Sorption characteristics of rosehip, apple and tomato pulp formulations as determined by gravimetric and hygrometric methods - Demarchi, Silvana María; Quintero Ruiz, Natalia Andrea; De Michelis, Antonio; Giner, Sergio Adrian (Elsevier, 2018)
The sorption characteristics of three formulations based on rosehip, apple and tomato pulp, added with saccharides, and aimed at preparing fruit leathers, were studied. Desorption isotherms were determined at 20 and 40 °C, both by the static gravimetric and the hygrometric method. Experimental isotherms were all J-shaped, as expected for rich-sugar matrices. A model previously developed for apple leather isotherms, the GAB equation and the Halsey model were fitted to the gravimetric data. Hygrometric isotherms exhibited a typical behavior at high moisture contents although, at lower values, the water activity readings were consistently higher than in the gravimetric method, and were never below 0.363. Apparently, the low-moisture, high-sugar samples behave as non-hygroscopic materials in the short times allowed by the hygrometric measurement, possibly due to the presence of crystallized sugars. On these grounds, the fast hygrometric method appears to be unsuitable to measure the water activity of such samples.